Implementation and Feedback Analysis of Jigsaw Active Learning Method - Dhage, J. R.; Patil, M. S.; Pawar, A. B. (Journal of Engineering Education Transformations, 2017)
Engineering students are expected to be proactive, creative, confident, flexible -who can solve problems, make decisions, think critically, communicate ideas effectively and work efficiently within teams and groups. For rapidly changing world "knowing the knowledge" is not sufficient but knowledge should be applied in real time situation. This requirement is fulfilled by engineers who possess the above mentioned skill set, which are achieved by shifting to active learning methodology from traditional passive teaching methodology. The lifelong learning and potential knowledge can be achieved by active learning methods, as involvement of student is ensured in these methods compared to the traditional passive teaching methods. This paper discusses some issues related to traditional teaching methods and ways to overcome these issues by adapting active learning methods. Also the result of one of the active learning method i.e. Jigsaw technique is discussed in this paper. "Instruction begins when you, the teacher, learn from the learner. Put yourself in his place so that you may understand what he learns and the way he understands it." (Kierkegaard)